Apical hypertrophic cardiomyopathy associated with circumflex to left ventricular fistulae: a case report of two rare subtypes of rare conditions occurring together. Issue 2 (12th January 2021) - Conway, Samuel; Herrey, Anna S; Rakhit, Roby D
Abstract: Background : Coronary arterial fistulae are rare yet have been associated with hypertrophic cardiomyopathy (HCM). We present a patient who was found to have a left circumflex (LCx) to left ventricular (LV) fistula in combination with apical HCM. Case summary : A 72-year-old female presented with syncope after exercise. She sustained facial injuries including fracture of her nasal bones. There were no previous episodes, no cardiac history, and she denied chest pain or anginal symptoms. Electrocardiogram showed sinus rhythm with T-wave inversion throughout the chest leads. Echocardiography suggested apical HCM with hypertrophy of the LV apex but good systolic function. This was confirmed on cardiac magnetic resonance imaging with a characteristically spade-shaped LV cavity. Coronary angiography demonstrated a distal LCx to LV fistula from the apical hypertrophy but no coronary artery disease. She was started on beta-blockers and has had no further episodes, remaining well. Discussion : Coronary fistulae are present in 0.002% of the population but clinical outcomes are poorly understood. The majority are asymptomatic but anginal chest pains can occur through the 'coronary steal' phenomenon. Apical HCM is a subtype of HCM characterized by spade-shaped LV cavity obliteration. It is unclear whether the association between fistulae and HCM occur because of the increased vascularization and fibrosis associated with HCM or whether congenital malformation leads to hypertrophy. Both can produce a constellation of cardiac symptoms. Our patient has the previously unreported combination of apical HCM and an LCx fistula; two rarer subtypes of rare conditions appearing together.